Shorter and longer durations of sleep are associated with an increased twelve-month prevalence of psychiatric and substance use disorders: Findings from a nationally representative survey of US adults (NESARC-III). (May 2020) - Geoffroy, Pierre A.; Tebeka, Sarah; Blanco, Carlos; Dubertret, Caroline; Le Strat, Yann
Abstract: The lack of comprehensive data on the association between psychiatric and substance use disorders and habitual sleep duration represents a major health information gap. This study examines the 12-month prevalence of mental disorders stratified by duration of sleep. Data were drawn from face-to-face interviews conducted in the National Epidemiologic Survey on Alcohol and Related Conditions III, a nationally representative survey of US adults (N = 36, 309). There were 1893 (5.26%) participants who reported <5h of sleep/night; 2434(6.76%) 5 h/night; 7621(21.17%) 6 h/night; 9620(26.72%) 7 h/night; 11, 186(31.07%) 8 h/night, and 3245(9.01%) ≥9 h/night. A U-shaped association was observed between sleep duration and all mental disorders. The prevalence of mental disorders was 55% for individuals with <5 h/night and 47.81% for ≥9 h/night, versus 28.24% for the 7 h/night (aOR = 1.90 and 1.39 respectively). The greatest odds ratios were for the <5 h/night group, with an increased risk above 3-fold for panic disorder (PD), post-traumatic stress disorder (PTSD), psychotic disorder, and suicide attempt; between 2 and 3 fold for major depressive disorder (MDD), bipolar disorder (BD), and generalized anxiety disorder (GAD); and between 1 and 2 fold for tobacco and drug use disorders, specific and social phobias. The ≥9 h/night group had an increased risk above 1 to 2-fold regarding tobacco and drug use disorders, MDD, BD, PD, social phobia, GAD, PTSD, psychotic disorder, and suicide attempt. U-shaped associations exist between sleep duration and mental disorders, calling for respect to recommendations for adequate sleep duration in routine clinical care as well as to actions for primary prevention in public health settings. Highlights: This study present nationally representative data on the prevalence of mental disorders stratified by duration of sleep. A U-shaped association was observed between sleep duration and all psychiatric and substance use disorders. Highest risks, exceeding a 3-fold increase for some mental disorders, were observed for short sleepers, especially for the <5h/night group. Adequate sleep duration may have general clinical benefits, calling for actions for primary prevention in public health settings.